2014
DOI: 10.1177/0959683614561887
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoenvironmental changes in Central Europe (NE Poland) during the last 6200 years reconstructed from a high-resolution multi-proxy peat archive

Abstract: Peat deposits from an ombrotrophic bog (north-eastern Poland) were analysed to reconstruct peatland development and environmental changes. This paper presents reconstructions of hydrological changes and plant succession over the last 6000 years. The methods included the high-resolution analysis of plant macrofossils, pollen and testate amoebae, supported by radiocarbon dating. Three main phases were identified in the history of the bog and surrounding woodland vegetation: 4000–400 BC, 400 BC–AD 1700 and AD 170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…Most surprisingly, studies using varved lake sediments are missing despite their demonstrated potential for quantitative seasonal paleoclimate studies (Amann et al, 2014;Bonk et al, 2015;Larocque-Tobler et al, 2015). Recent work has also highlighted the potential of raised bogs as paleoenvironmental and paleoclimate archives in Poland (De Vleeschouwer et al, 2009;Gałka et al, 2014;Lamentowicz et al, 2015). …”
Section: Introductionmentioning
confidence: 93%
“…Most surprisingly, studies using varved lake sediments are missing despite their demonstrated potential for quantitative seasonal paleoclimate studies (Amann et al, 2014;Bonk et al, 2015;Larocque-Tobler et al, 2015). Recent work has also highlighted the potential of raised bogs as paleoenvironmental and paleoclimate archives in Poland (De Vleeschouwer et al, 2009;Gałka et al, 2014;Lamentowicz et al, 2015). …”
Section: Introductionmentioning
confidence: 93%
“…The profiles have a thickness of 800, 835 and 600 cm, respectively. For better time control, we used absolute chronologies (Gałka et al, 2015(Gałka et al, , 2017Lamentowicz et al, 2015), refined by Kołaczek et al (2019). In the case of Gz, in which 14 C date inversions have been detected, the model with the highest agreement index and the lowest number of excluded dates was selected (Supplementary Data 1, available online).…”
Section: Methodsmentioning
confidence: 99%
“…The NPP composition was determined in the samples subjected to standard laboratory procedures including acetolysis, the same ones as those designated to palynological analysis in previous studies (Gałka et al, 2015(Gałka et al, , 2017Lamentowicz et al, 2015). As the Lycopodium tablets were added to samples (Stockmarr, 1971) and counted during both pollen and NPP investigations, it was possible to combine NPP and pollen data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Russia contains one of the largest areas of peatland in the world [24], there were remarkably few peat-based palaeoecological studies using proxies other than pollen [7,[25][26][27]. In particular, raised bogs in the East European Plain are affected by the continental climate conditions in contrast with better studied Atlantic or Baltic raised bogs of Northern, Western and Eastern Europe [28][29][30][31]. Past human impact on these ecosystems that cover large areas in this region [24] is also insufficiently recognized.…”
Section: Introductionmentioning
confidence: 99%